Tupuna Awa: People and Politics of the Waikato River - Muru-Lanning, Marama (Auckland University Press, 2016)
'We have always owned the water . . . we have never ceded our mana over the river to anyone', King Tuheitia Paki asserted in 2012. Prime Minister John Key disagreed: ‘King Tuheitia's claim that Maori have always owned New Zealand's water is just plain wrong'. So who does own the water in New Zealand – if anyone – and why does it matter? Offering some human context around that fraught question, Tupuna Awa looks at the people and politics of the Waikato River. For iwi and hapu of the lands that border its 425-kilometre length, the Waikato River is an ancestor, a taonga and a source of mauri, lying at the heart of identity and chiefly power. It is also subject to governing oversight by the Crown and intersected by hydro-stations managed by state-owned power companies: a situation rife with complexity and subject to shifting and subtle power dynamics. Marama Muru-Lanning explains how Maori of the region, the Crown and Mighty River Power have talked about the ownership, guardianship and stakeholders of the river. By examining the debates over water in one New Zealand river, over a single recent period, Muru-Lanning provides a powerful lens through which to view modern iwi politics, debates over water ownership, and contests for power between Maori and the state.
Keywords: iwi politics; water ownership